Terapi Radiasi Eksternal dengan Metode Hypofractionated pada Kanker payudara Post Breast Conserving Surgery di Instalasi Onkologi Radiasi Rumah Sakit Indriati Solo Baru: Studi Kasus - Rorong, Fabrizio Alessandro; Prasetya, I Made Lana; Juliasa, I Wayan (Jurnal Imejing Diagnostik (JImeD), 2025)
Background: Radiotherapy is one method of cancer treatment that uses radiation to destroy cancer cells. Radiation dose delivery is done gradually through a process called fractionation, which is divided into conventional and hypofractionated fractions. In the radiation oncology installation of the new Indriati Solo Hospital, some breast cancer patients have received treatment with the hypofractionated method, while the majority still use the conventional fraction method. The hypofractionated method aims to reduce the number of treatment sessions by increasing the dose in each fraction with outcomes comparable to conventional fractions.Methods: This research method is descriptive qualitative with a case study approach. The study involves breast cancer patients post-Breast Conserving Surgery (BCS), Data were gathered through interviews with radiation oncologists, radiotherapists, and medical physicists, along with direct observations and patient record analysis The collected data were analyzed descriptively to evaluate the application and effectiveness of the hypofractionated method.Results: The results showed that the use of hypofractionated can shorten OTT (Overall Treatment Time), as well as better side effects than conventional fractions, and effectively reduce the number of queues of radiotherapy patients. In conclusion, the use of the hypofractionated method is very effective and recommended for radiotherapy treatment in breast cancer.Conclusions: Hypofractionated radiotherapy for breast cancer patients at Indriati Solo Baru has proven effective in reducing OTT and patient queues, with outcomes comparable to conventional fractionation. Further research is needed to assess long-term benefits, including quality of life, recurrence rates, cost-effectiveness, and dose distribution, particularly in high-volume healthcare settings. Hypofractionated radiotherapy is a promising alternative.